The Influence of Work Involvement, Job Satisfaction and Affective Commitment on ASN Employee Loyalty: A Case Study at the Semarang Regency Regional Secretariat Office - Suci, Salsa Bila Febriana Eka; Fauzan, Mohammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this study is (1) to clarify and assess the impact of work engagement on the job loyalty of civil servants (ASN); (2) to elucidate and assess the effect of job satisfaction on the job loyalty of ASN employees; (3) to expound and evaluate the influence of organizational commitment on the job loyalty of ASN employees. This research falls within the explanatory research category. The study encompasses a population of 91 ASN employees at the Secretariat Office of Semarang Regency, with all members of the population being included as participants (census method). Data were collected through Google Form applications distributed to the respondents. To analyze the data, Instrument Test, Model Test, and Hypothesis Test were conducted, and SPSS software was used for data processing. The research outcomes reveal that (1) work engagement positively impacts the loyalty of ASN employees, (2) job satisfaction does not have a significant effect on the loyalty of ASN employees, and (3) affective commitment has a favorable influence on the loyalty of ASN employees at the Secretariat Office of Semarang Regency.